Biochar-loaded nano zero-valent iron material for removing chlorinated hydrocarbon in water and preparation method thereof
By forming a multi-layered structure and vertical nanotube-shaped morphology on biochar and forming a nano zero-valent iron structure by electrochemical methods, the problem of nano zero-valent iron agglomeration is solved, and the removal efficiency of chlorinated hydrocarbons and material stability is improved. It achieves efficient removal of chlorinated hydrocarbons in water.
Patent Information
- Application Number
- CN202411563408.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-05
- Publication Date
- 2025-01-14
AI Technical Summary
When existing biochar-loaded nano zero-valent iron materials remove chlorinated hydrocarbons in water, nano zero-valent iron is prone to agglomeration, which reduces the specific surface area and reactivity, affects the removal efficiency, and has poor stability, and is inconsistent in targeted removal efficiency.
By forming a multi-layered structure on biochar, perpendicular to the nanotube-shaped form, and using electrochemical methods to form a vertical nanotube zero-valent iron structure on the surface of biochar, the dispersion degree and electrochemical performance of nano-valent iron are improved, combined with Multi-layer processing and modification treatment form composite materials to improve removal efficiency.
The specific surface area and reactivity of biochar-loaded nano zero-valent iron materials are improved, and the removal efficiency of chlorinated hydrocarbons in water is significantly improved, especially the degradation rate of trichloroethylene, and the stability and targeted treatment capacity of the material are enhanced.
Smart Images

Figure BDA0005118540770000081 
Figure BDA0005118540770000091
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of biochar materials, and in particular to a biochar-loaded nanometer zero-valent iron material for removing chlorinated hydrocarbons in water and a preparation method thereof. Background Art
[0002] Chlorinated hydrocarbons are an important chemical raw material and are widely used in industrial cleaning, clothing degreasing and other fields. However, due to the unreasonable discharge of industrial wastewater and domestic sewage, the leakage of leachate from waste accumulation sites, and the leakage of toxic and hazardous chemical wastes, chlorinated hydrocarbons have become one of the most common toxic and hazardous pollutants in groundwater. This pollution seriously affects human health and ecological environmental safety. Biochar-loaded nano-zero-valent iron (BC / nZVI) material is an emerging environmental remediation material that combines the high specific surface area of biochar with the high reduction activity of nano-zero-valent iron. This composite material shows excellent performance in removing heavy metals, organic pollutants and persistent organic pollutants from water.
[0003] In the existing technology, when biochar-loaded nano zero-valent iron materials are used to remove chlorinated hydrocarbons in water, the nano zero-valent iron is usually prone to agglomeration in the water environment, which will reduce its effective specific surface area and reaction activity, thereby affecting the removal efficiency. In addition, the stability is poor and the specificity needs to be improved. The removal efficiency of BC / nZVI for various pollutants in water may vary, resulting in low treatment efficiency and other problems. Summary of the invention
[0004] In order to solve the above problems, the present invention provides a biochar-loaded nano zero-valent iron material for removing chlorinated hydrocarbons in water and a preparation method thereof.
[0005] A biochar-loaded nano zero-valent iron material for removing chlorinated hydrocarbons in water. In the biochar-loaded nano zero-valent iron material, the structure of the biochar is multi-layered, the structure of the zero-valent iron is in the form of nanotubes perpendicular to the biochar layers, the multi-layered biochar includes multiple biochar levels with multiple pore sizes, and the loading amount of the nano zero-valent iron on the biochar is 5 to 12 wt%.
[0006] Description: The biochar-loaded nano zero-valent iron material of the above structure can reduce the agglomeration problem of nano zero-valent iron through the nanotube morphology perpendicular to the hierarchical structure of the biochar, thereby increasing the specific surface area and reaction activity of the material, thereby improving the efficiency of removing chlorinated hydrocarbons in water. At the same time, the structure can enhance the adsorption effect of chlorinated hydrocarbons in water and improve the removal efficiency.
[0007] The present invention also provides a method for preparing a biochar-loaded nanometer zero-valent iron material for removing chlorinated hydrocarbons in water, comprising the following steps:
[0008] S1, adding biomass into methanol and mixing, wherein the concentration of biomass in methanol is 5-10wt%, and forming a uniform mixed solution through stirring and ultrasonic treatment;
[0009] S2, adding 0.5-1 wt% glutaraldehyde to the mixed solution, stirring at room temperature for 5-6 hours to form a gel and drying to obtain a solid;
[0010] S3, then pyrolyzing the solid in an inert atmosphere, the pyrolysis temperature is 500-900° C., the heating rate is 5-10° C. / min, and the insulation time is 1-3 h to obtain pretreated biochar;
[0011] S4, adding the pretreated biochar to a sodium hydroxide aqueous solution with a mass concentration of 5-10% at a mass ratio of 1:10-13, heating to 150-250°C and standing for 4-8 hours, then starting ultrasonic treatment for 30-60 minutes; then washing and drying to obtain layered biochar;
[0012] S5. In a system where the cathode material is the layered biochar and the anode material is a platinum sheet electrode, the electrolyte is a ferrous sulfate solution with a concentration of 0.1 to 0.2 mol / L, the layered biochar surface is covered with a layer of cellulose film, and the current density is set to 10 to 15 mA / cm 2 After electrolysis for 1 to 3 hours, the cathode material is taken out, cleaned, and dried to obtain a biochar-loaded nano zero-valent iron material.
[0013] Description: The above method can use electrochemical methods to form a vertical nanotube zero-valent iron structure on the surface of biochar with good dispersion. In addition, the electrochemical properties and specific surface area of the material obtained by the above method are excellent. Since the electrochemical properties and specific surface area have a significant impact on the efficiency of removing chlorinated hydrocarbons, improving the electrochemical properties of the material can greatly improve its removal efficiency for chlorinated hydrocarbons, especially trichloroethylene.
[0014] Furthermore, the biomass described in S1 is one or more of bamboo powder, coconut shell, walnut shell, straw, bagasse and catkins.
[0015] Note: The above raw materials are all common raw materials for biochar.
[0016] Furthermore, the drying temperature in S2 is 50-60° C., the stirring speed is 300-400 r / min, and the stirring time is 15-25 min.
[0017] Note: The above temperature is more suitable. Low-temperature drying at 50-60°C can reduce the damage to biochar and gel, which may cause its morphology to be uncontrollable.
[0018] Furthermore, in S1, the stirring speed is 300-400 r / min, the stirring time is 15-25 min, the ultrasonic frequency in the ultrasonic treatment is 40-45 kHz, the ultrasonic power is 200-300 W, and the ultrasonic treatment time is 30-60 min; in S4, the ultrasonic frequency is 30-35 kHz, and the ultrasonic power is 200-300 W.
[0019] Note: The above ultrasonic parameters can promote the uniform dispersion of ferrous sulfate, so that after the iron ions are reduced to zero-valent iron on the surface of biochar, they are evenly distributed and deposited on the surface of biochar to form nano zero-valent iron.
[0020] Furthermore, the thickness of the cellulose membrane is 100-150 μm, the porosity of the cellulose membrane is 34-40%, and the pore size is 1-10 μm.
[0021] Note: The above-mentioned cellulose membrane can act as a template to make the nano-zero-valent iron on the surface of biochar regular and nano-tubular in shape. The material obtained by the above-mentioned cellulose membrane parameters has a better effect of removing chlorinated hydrocarbons in water.
[0022] Furthermore, the cathode material is prepared by coating the layered biochar on a conductive titanium mesh, and the thickness of the layered biochar coating is 300 to 400 μm.
[0023] Note: The material obtained with the above parameters has a better effect in removing chlorinated hydrocarbons from water.
[0024] Furthermore, it also includes: S6, subjecting the biochar-loaded nano zero-valent iron material to a multi-layer treatment; the multi-layer treatment method is to coat the biochar-loaded nano zero-valent iron material on a substrate, the substrate being the conductive titanium mesh, and then coating a layer of the layered biochar on the surface of the biochar-loaded nano zero-valent iron material to form a secondary biochar-loaded nano zero-valent iron material, using the secondary biochar-loaded nano zero-valent iron material as the cathode material, using a ferrous sulfate solution with a concentration of 0.1 to 0.2 mol / L as the electrolyte, and at a current density of 5 to 8 mA / cm 2 After electrolysis for 30 to 50 minutes, the product is taken out, cleaned and dried to obtain a multi-layered biochar composite nano zero-valent iron material.
[0025] The thickness of the biochar-loaded nano zero-valent iron material coated on the conductive titanium mesh is 100-180 μm, and the thickness of the layered biochar coated on the surface of the biochar-loaded nano zero-valent iron material is 80-90 μm.
[0026] Description: The above method can form a two-layer structure of biochar loaded with nano zero-valent iron. This structure can utilize a multi-level composite structure to strengthen the three-dimensional structural morphology of the material, thereby having a higher specific surface area and a better effect of removing chlorinated hydrocarbons.
[0027] Furthermore, the layered biochar is subjected to a modification treatment, and the modification treatment method comprises:
[0028] S4-1. PVA is added to deionized water at a ratio of 10-15 g: 90 ml, stirred at a temperature of 80 ° C and a stirring speed of 200-300 rpm until a transparent PVA solution is formed. The layered biochar is added to the PVA solution at a ratio of 1-2 g: 90 ml and allowed to stand for 2-4 hours, then filtered, washed, and pre-dried:
[0029] S4-2, heat the pre-dried biochar to 120-150°C at a heating rate of 4-5°C / min, and keep the temperature constant for 1-2 hours; the modification treatment is completed.
[0030] Description: The above method can be used to modify biochar. Polyvinyl alcohol forms chemical bonds between the layers of layered biochar, thereby fixing the multi-level structure and giving it a variety of pores. A complex layer and pore morphology has been formed to improve the material's treatment effect on chlorinated hydrocarbons in water.
[0031] Furthermore, when the layered biochar is added to the PVA solution, a polysilane-polydopamine copolymer is added in an amount of 2 to 3% by volume of the PVA solution.
[0032] Description: The polysilane-polydopamine copolymer has π-π stacking effects on the surface of layered biochar, which can further achieve surface modification of biochar and improve the surface hydrophobicity and chemical stability of biochar.
[0033] The beneficial effects of the present invention are:
[0034] The biochar-loaded nano zero-valent iron material of the structure of the present invention is pre-arranged in a nanotube-shaped form perpendicular to the hierarchical structure of the biochar, which can reduce the agglomeration problem of nano zero-valent iron, thereby increasing the specific surface area and reaction activity of the material, thereby increasing the efficiency of removing chlorinated hydrocarbons in water. At the same time, the structure can enhance the adsorption effect of chlorinated hydrocarbons in water and improve the removal efficiency. At the same time, in the preparation method of the present invention, a vertical nanotube zero-valent iron structure is formed on the surface of the biochar by an electrochemical method, and the degree of dispersion is good. In addition, the electrochemical performance and specific surface area of the material obtained by the above method are both excellent. Since the electrochemical performance and specific surface area have a significant influence on the efficiency of removing chlorinated hydrocarbons, the removal efficiency of chlorinated hydrocarbons, especially trichloroethylene, can be greatly improved by improving the electrochemical characteristics of the material. DETAILED DESCRIPTION
[0035] In order to further illustrate the method adopted by the present invention and the effect achieved, the technical solution of the present invention will be clearly and completely described in combination with experiments below.
[0036] Example 1: A biochar-loaded nano zero-valent iron material for removing chlorinated hydrocarbons in water. In the biochar-loaded nano zero-valent iron material, the structure of the biochar is multi-layered, the structure of the zero-valent iron is nanotube-shaped perpendicular to the biochar layer, the multi-layered biochar includes multiple biochar levels with multiple pore sizes, and the loading amount of the nano zero-valent iron on the biochar is 6wt%.
[0037] A method for preparing a biochar-loaded nanometer zero-valent iron material for removing chlorinated hydrocarbons in water comprises the following steps:
[0038] S1. Add biomass to methanol and mix them. The concentration of biomass in methanol is 8wt%, and a uniform mixed solution is formed by stirring and ultrasonic treatment. The biomass is bamboo powder and catkins with a mass ratio of 1:1. The stirring speed is 350r / min, the stirring time is 20min, the ultrasonic frequency in the ultrasonic treatment is 42kHz, the ultrasonic power is 240W, and the ultrasonic treatment time is 40min.
[0039] S2, add 0.8wt% glutaraldehyde to the mixed solution, stir at room temperature for 5.5h to form a gel and dry to obtain a solid; the drying temperature is 55°C; the stirring speed is 350r / min, and the stirring time is 20min;
[0040] S3, then pyrolyzing the solid in an inert atmosphere, the pyrolysis temperature is 700° C., the heating rate is 8° C. / min, and the insulation time is 2 h to obtain pretreated biochar; the inert atmosphere is nitrogen;
[0041] S4, adding the pretreated biochar to an aqueous sodium hydroxide solution with a mass concentration of 8% at a mass ratio of 1:12, heating to 200°C and standing for 6 hours, then starting ultrasonic treatment for 40 minutes; then washing and drying to obtain layered biochar; the ultrasonic frequency is 32kHz, and the ultrasonic power is 250W;
[0042] S5. In a system where the cathode material is the layered biochar and the anode material is a platinum sheet electrode, the electrolyte is a 0.15 mol / L ferrous sulfate solution, the layered biochar surface is covered with a cellulose film, and the current density is set to 12 mA / cm 2After electrolysis for 2 hours, the cathode material is taken out, washed and dried to obtain a biochar-loaded nano zero-valent iron material; the thickness of the cellulose membrane is 120 μm, the porosity of the cellulose membrane is 38%, and the pore size is 5 μm; the cathode material is prepared by coating the layered biochar on a conductive titanium mesh, and the thickness of the layered biochar coating is 350 μm;
[0043] In the above cleaning and drying, the drying temperature was 55°C, and the cleaning was performed by rinsing with clean water 3 times.
[0044] Example 2: This example is different from Example 1 in that the raw material components are different. In S1, the concentration of biomass in methanol is 5wt%; in S2, 0.5wt% of glutaraldehyde is added to the mixed solution; in S4, the pretreated biochar is added to sodium hydroxide at a mass ratio of 1:13; in S5, the electrolyte is a ferrous sulfate solution with a concentration of 0.1mol / L.
[0045] Example 3: This example is different from Example 1 in that the raw material components are different. In S1, the concentration of biomass in methanol is 10wt%; in S2, 1wt% glutaraldehyde is added to the mixed solution; in S4, the pretreated biochar is added to sodium hydroxide at a mass ratio of 1:10; in S5, the electrolyte is a ferrous sulfate solution with a concentration of 0.2mol / L.
[0046] Example 4: This example is different from Example 1 in that the temperature parameters are different. The pyrolysis temperature in S3 is 500°C and the heating rate is 10°C / min; the temperature in S4 is increased to 150°C; the drying temperatures of S1, S2, S3, and S4 are all 50°C.
[0047] Example 5: This example is different from Example 1 in that the temperature parameters are different. The pyrolysis temperature in S3 is 900°C and the heating rate is 5°C / min; the temperature in S4 is increased to 250°C; the drying temperatures of S1, S2, S3, and S4 are all 60°C.
[0048] Example 6: The difference between this example and Example 1 is that the time parameters are different. The stirring time in S1 is 15 min; the ultrasonic treatment time is 60 min; S2 is stirred at room temperature for 5 h, the stirring speed is 300 r / min, and the stirring time is 25 min; the insulation time in S3 is 1 h; S4 is heated to 200°C and allowed to stand for 8 h, and then the ultrasonic treatment is turned on for 30 min; S5 is electrolyzed for 3 h.
[0049] Example 7: The difference between this example and Example 1 is that the time parameters are different. The stirring time in S1 is 25 min; the ultrasonic treatment time is 30 min; S2 is stirred at room temperature for 6 h, the stirring speed is 400 r / min, and the stirring time is 15 min; the insulation time in S3 is 3 h; S4 is heated to 200°C and allowed to stand for 4 h, and then the ultrasonic treatment is turned on for 60 min; S5 is electrolyzed for 1 h.
[0050] Example 8: This example is different from Example 1 in that the ultrasonic frequency in S1 is 45kHz, the ultrasonic power is 200W; the ultrasonic frequency in S4 is 30kHz, the ultrasonic power is 200W, and the mass concentration of the sodium hydroxide aqueous solution is 10%; the current density in S5 is 10mA / cm 2 .
[0051] Example 9: This example is different from Example 1 in that the ultrasonic frequency in S1 is 40kHz, the ultrasonic power is 300W; the ultrasonic frequency in S4 is 35kHz, the ultrasonic power is 300W, and the mass concentration of the sodium hydroxide aqueous solution is 5%; the current density in S5 is 15mA / cm 2 .
[0052] Example 10: This example is different from Example 1 in that the thickness of the cellulose membrane is 100 μm, the porosity of the cellulose membrane is 34%, and the pore size is 10 μm; the preparation method of the cathode material is: coating the layered biochar on a conductive titanium mesh, and the thickness of the layered biochar coating is 300 μm.
[0053] Example 11: This example is different from Example 1 in that the thickness of the cellulose membrane is 150 μm, the porosity of the cellulose membrane is 40%, and the pore size is 1 μm; the preparation method of the cathode material is: coating the layered biochar on a conductive titanium mesh, and the thickness of the layered biochar coating is 400 μm.
[0054] Embodiment 12: This embodiment is different from Embodiment 1 in that the method further comprises:
[0055] S6, subjecting the biochar loaded with nano zero-valent iron material to a multi-layer treatment; the multi-layer treatment method is:
[0056] The biochar-loaded nano zero-valent iron material is coated on a substrate, the substrate is the conductive titanium mesh, and then a layer of the layered biochar is coated on the surface of the biochar-loaded nano zero-valent iron material to form a secondary biochar-loaded nano zero-valent iron material. The secondary biochar-loaded nano zero-valent iron material is used as the cathode material, and a 0.15 mol / L ferrous sulfate solution is used as the electrolyte. At a current density of 6 mA / cm 2After electrolysis for 40 min, the product was taken out, cleaned and dried to obtain a multi-layered biochar composite nano zero-valent iron material.
[0057] The thickness of the biochar-loaded nano zero-valent iron material coated on the conductive titanium mesh is 150 μm, and the thickness of the layered biochar coated on the surface of the biochar-loaded nano zero-valent iron material is 85 μm.
[0058] Example 13: This example is different from Example 12 in that the electrolysis parameters are different. At a current density of 5 mA / cm 2 After electrolysis for 50 minutes, take it out.
[0059] Example 14: This example is different from Example 12 in that the electrolysis parameters are different. At a current density of 8 mA / cm 2 After electrolysis for 30 minutes, take it out.
[0060] Example 15: This example is different from Example 12 in that the loading parameters are different. The thickness of the biochar-loaded nano zero-valent iron material coated on the conductive titanium mesh is 100 μm, and the thickness of the layered biochar coated on the surface of the biochar-loaded nano zero-valent iron material is 90 μm.
[0061] Example 16: This example is different from Example 12 in that the loading parameters are different. The thickness of the biochar-loaded nano zero-valent iron material coated on the conductive titanium mesh is 180 μm, and the thickness of the layered biochar coated on the surface of the biochar-loaded nano zero-valent iron material is 80 μm.
[0062] Example 17: This example is different from Example 1 in that the layered biochar is modified, and the modification method includes:
[0063] S4-1. PVA was added to deionized water at a ratio of 13 g: 90 ml, and stirred at a temperature of 80 ° C and a stirring speed of 250 rpm until a transparent PVA solution was formed. The layered biochar was added to the PVA solution at a ratio of 1.5 g: 90 ml and allowed to stand for 3 hours, and then filtered, washed, and pre-dried:
[0064] S4-2. The pre-dried biochar was heated to 130°C at a heating rate of 4°C / min and kept at a constant temperature for 1.5 hours. The modification treatment was completed.
[0065] Example 18: This example is different from Example 17 in that the processing parameters are different. S4-1. PVA is added to deionized water at a ratio of 10 g: 90 ml, and stirred at 80°C and 200 rpm until a transparent PVA solution is formed. The layered biochar is added to the PVA solution at a ratio of 2 g: 90 ml, and allowed to stand for 4 hours, and then filtered, washed, and pre-dried. S4-2. The pre-dried biochar is heated to 120°C at a heating rate of 5°C / min and treated at a constant temperature for 2 hours. The modification treatment is completed.
[0066] Example 19: This example is different from Example 17 in that the processing parameters are different. S4-1. PVA is added to deionized water at a ratio of 15 g:90 ml, and stirred at 80°C and 300 rpm until a transparent PVA solution is formed. The layered biochar is added to the PVA solution at a ratio of 1 g:90 ml, and allowed to stand for 2 hours, and then filtered, washed, and pre-dried. S4-2. The pre-dried biochar is heated to 150°C at a heating rate of 4°C / min and treated at a constant temperature for 1 hour. The modification treatment is completed.
[0067] Example 20: This example is different from Example 17 in that when the layered biochar is added to the PVA solution, a polysilane-polydopamine copolymer is added at a volume fraction of 3% of the PVA solution.
[0068] Example 21: This example differs from Example 20 in that a polysilane-polydopamine copolymer is added at a volume fraction of 2% of the PVA solution.
[0069] Experimental Example: The description of this experimental example is based on the scheme described in Example 1, and is intended to illustrate the practical application effect of the present invention.
[0070] 1. Prepare 500 mL of 30 mg / L trichloroethylene solution, add 100 mg of the biochar-loaded nano zero-valent iron material obtained in Examples 1 to 21, and degrade at room temperature for 2 days. Test the concentration of trichloroethylene in the solution to obtain the actual degradation rate of trichloroethylene. The test results are as follows:
[0071] 1. To explore the effect of biochar-loaded nano-zero-valent iron materials obtained by different treatment methods on the degradation rate of trichloroethylene in water;
[0072] Comparative Example 1: The difference from Example 1 is that the biochar-loaded nano zero-valent iron material obtained by the method of patent CN110586038A is used for the experiment.
[0073] Example 1, Example 2 and Example 3, Example 15 and Example 16, and Comparative Example 1 are compared, as shown in Table 1;
[0074] Table 1 Experimental results of degradation rate of trichloroethylene in water by biochar loaded with nano zero-valent iron materials obtained by different treatment methods
[0075] parameter Degradation rate % Example 1 80 Example 12 85 Embodiment 17 86 Embodiment 20 89 Comparative Example 1 67
[0076] As can be seen from Table 1, by comparing Example 1 with Comparative Example 1, it can be seen that the biochar-loaded nano zero-valent iron material obtained by the preparation method in Example 1 has a higher degradation rate of trichloroethylene in water. This may be because the biochar and zero-valent iron obtained by the preparation method in Example 1 have better structures themselves and provide a larger specific surface area, and the electrochemical performance in the method in Example 1 is better, which improves the activity of the material surface, thereby making the removal efficiency of trichloroethylene higher.
[0077] By comparing Example 1 with Example 12, it can be seen that compared with the method in Example 1, the biochar-loaded nano zero-valent iron material in Example 1 is subjected to multi-layer treatment to form a two-layer composite multi-layer biochar composite nano zero-valent iron material. This structure can further optimize the conformity between biochar and nano zero-valent iron, forming a composite material with nano zero-valent iron as a connecting tube and two biochar layers. This composite material has a better three-dimensional morphology and a higher degradation rate.
[0078] By comparing Example 1 with Example 17, it can be seen that compared with the method in Example 1, the modification treatment in Example 17 has a good effect. In Example 17, PVA (polyvinyl alcohol) is used to modify the biochar. Since polyvinyl alcohol can form chemical bonds between the layers of the layered biochar, the multi-layer structure can be fixed. At the same time, polyvinyl alcohol can play the role of a cross-linking agent, which can make the biochar produce a variety of pores and form a complex layer and pore morphology to improve the material's treatment effect on chlorinated hydrocarbons in water.
[0079] By comparing Example 17 with Example 20, it can be seen that compared with the method of Example 17, after the polysilane-polydopamine copolymer is added in Example 20, trichloroethylene has a more obvious effect. This may be because the polysilane-polydopamine copolymer has π-π stacking effects on the surface of the layered biochar, further realizing the surface modification of the biochar, improving the surface hydrophobicity and chemical stability of the biochar, thereby improving the degradation effect on trichloroethylene.
[0080] 2. To explore the effect of biochar-loaded nano-zero-valent iron materials obtained with different preparation parameters on the degradation rate of trichloroethylene in water;
[0081] Example 1 and Examples 2-19 were compared, as shown in Table 2;
[0082] Table 2 Effect of biochar-loaded nano-zero-valent iron materials obtained with different preparation parameters on the degradation rate of trichloroethylene in water
[0083]
[0084]
[0085] As can be seen from Table 2, by comparing Example 1, Example 2 and Example 3, it can be seen that the raw material components of Example 1 are more preferred, and the raw material matching of Example 1 is more reasonable. Exceeding this range may lead to deviations in the formed material structure (unable to form a regular hierarchy and nanotube zero-valent iron structure). By comparing Example 1, Example 4 and Example 5, it can be found that the temperature parameters of Example 1 are more preferred. At this temperature, the surface state of the material is the best. Exceeding this range may lead to a decrease in the surface activity of the material; by comparing Example 1, Example 6 and Example 7, it can be found that the time parameters of Example 1 are more preferred; by comparing Example 1, Example 8 and Example 9, it can be found that the ultrasonic frequency of Example 1 is more preferred; by comparing Example 1, Example 10 and Example 11, it can be found that the parameters of the cellulose membrane and the cathode material of Example 1 are more preferred. Under this parameter, a biochar-loaded nano zero-valent iron material with a suitable size ratio can be formed to ensure its effect of degrading chlorinated hydrocarbons; by comparing Example 12 in Table 1 and Example 13 and Example 14 in Table 2, it can be seen that the parameters in Example 12 are better; by comparing Example 17, Example 18 and Example 19, the modification parameters in Example 17 are better.
Claims
1. A biochar-loaded nanometer zero-valent iron material for removing chlorinated hydrocarbons from water, characterized in that: In the biochar-loaded nano zero-valent iron material, the biochar has a multi-layered structure, the zero-valent iron has a nanotube structure perpendicular to the biochar layer, the multi-layered biochar includes multiple biochar levels with multiple pore sizes, and the loading amount of the nano zero-valent iron on the biochar is 5 to 12 wt%.
2. The method for preparing a biochar-loaded nano zero-valent iron material for removing chlorinated hydrocarbons in water according to claim 1, characterized in that: The following steps are involved: S1, adding biomass into methanol and mixing, wherein the concentration of biomass in methanol is 5-10wt%, and forming a uniform mixed solution through stirring and ultrasonic treatment; S2, adding 0.5-1 wt% glutaraldehyde to the mixed solution, stirring at room temperature for 5-6 hours to form a gel and drying to obtain a solid; S3, then pyrolyzing the solid in an inert atmosphere, the pyrolysis temperature is 500-900° C., the heating rate is 5-10° C. / min, and the insulation time is 1-3 h to obtain pretreated biochar; S4, adding the pretreated biochar to a sodium hydroxide aqueous solution with a mass concentration of 5-10% at a mass ratio of 1:10-13, heating to 150-250°C and standing for 4-8 hours, then starting ultrasonic treatment for 30-60 minutes; then washing and drying to obtain layered biochar; S5. In a system where the cathode material is the layered biochar and the anode material is a platinum sheet electrode, the electrolyte is a ferrous sulfate solution with a concentration of 0.1 to 0.2 mol / L, the layered biochar surface is covered with a layer of cellulose film, and the current density is set to 10 to 15 mA / cm 2 After electrolysis for 1 to 3 hours, the cathode material is taken out, cleaned, and dried to obtain a biochar-loaded nano zero-valent iron material.
3. The method for preparing a biochar-loaded nano zero-valent iron material for removing chlorinated hydrocarbons in water according to claim 2, characterized in that: The biomass described in S1 is one or more of bamboo powder, coconut shell, walnut shell, straw, bagasse and catkins.
4. The method for preparing a biochar-loaded nano zero-valent iron material for removing chlorinated hydrocarbons in water according to claim 2, characterized in that: The drying temperature in S2 is 50-60° C., the stirring speed is 300-400 r / min, and the stirring time is 15-25 min.
5. The method for preparing a biochar-loaded nano zero-valent iron material for removing chlorinated hydrocarbons in water according to claim 2, characterized in that: In S1, the stirring speed is 300-400 r / min, the stirring time is 15-25 min, the ultrasonic frequency in the ultrasonic treatment is 40-45 kHz, the ultrasonic power is 200-300 W, and the ultrasonic treatment time is 30-60 min; in S4, the ultrasonic frequency is 30-35 kHz, and the ultrasonic power is 200-300 W.
6. The method for preparing a biochar-loaded nano zero-valent iron material for removing chlorinated hydrocarbons in water according to claim 2, characterized in that: The thickness of the cellulose membrane is 100-150 μm, the porosity of the cellulose membrane is 34-40%, and the pore size is 1-10 μm.
7. The method for preparing a biochar-loaded nano zero-valent iron material for removing chlorinated hydrocarbons in water according to claim 2, characterized in that: The cathode material is prepared by coating the layered biochar on a conductive titanium mesh, and the thickness of the layered biochar coating is 300-400 μm.
8. The method for preparing a biochar-loaded nano zero-valent iron material for removing chlorinated hydrocarbons in water according to claim 2, characterized in that: Also includes: S6, subjecting the biochar-loaded nano zero-valent iron material to a multi-layer treatment; The multi-layer processing method is: The biochar-loaded nano zero-valent iron material is coated on a substrate, the substrate is the conductive titanium mesh, and then a layer of the layered biochar is coated on the surface of the biochar-loaded nano zero-valent iron material to form a secondary biochar-loaded nano zero-valent iron material. The secondary biochar-loaded nano zero-valent iron material is used as the cathode material, and a ferrous sulfate solution with a concentration of 0.1 to 0.2 mol / L is used as the electrolyte. At a current density of 5 to 8 mA / cm 2 After electrolysis for 30 to 50 minutes, the product is taken out, cleaned and dried to obtain a multi-layered biochar composite nano zero-valent iron material. The thickness of the biochar-loaded nano zero-valent iron material coated on the conductive titanium mesh is 100-180 μm, and the thickness of the layered biochar coated on the surface of the biochar-loaded nano zero-valent iron material is 80-90 μm.
9. The method for preparing a biochar-loaded nano zero-valent iron material for removing chlorinated hydrocarbons in water according to claim 2, characterized in that: The layered biochar is modified, and the modification method includes: S4-1. PVA is added to deionized water at a ratio of 10-15 g: 90 ml, stirred at a temperature of 80 ° C and a stirring speed of 200-300 rpm until a transparent PVA solution is formed. The layered biochar is added to the PVA solution at a ratio of 1-2 g: 90 ml and allowed to stand for 2-4 hours, then filtered, washed, and pre-dried: S4-2, heat the pre-dried biochar to 120-150°C at a heating rate of 4-5°C / min, and keep the temperature constant for 1-2 hours; the modification treatment is completed.
Citation Information
Patent Citations
Biochar-loaded nano zero-valent iron material and application thereof
CN110586038A